Bhutan Diary 3– in the land of the Thunder Dragon the second face-to-face meeting - Chan Kit Yok, Margaret (UiTM Sarawak, 2018)
On 26 January 2018, Associate Professor Dr. Margaret Chan, the National Coordinator for Malaysia and Associate Professor Dr. Ling Siew Eng left Dhaka, Bangladesh for Paro, Bhutan to attend the second Blended Learning for Teacher Educators in Asia and Europe (BLTeae) project meeting. The following two days before the actual meeting gave the duo time to visit friends met during the earlier two trips to Bhutan.